Filsafat menjadi Alternatif Pencegah Kerusakan Lingkungan - Hardiansyah Hardiansyah (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
Man destructs and exploits nature and environment without or with giving  attention to the hurt or broken body of earth. Man is not wise toward nature and  environment. Does Philosophy could prevent the destructions, as it serves man to  become wise? Since philosophy turn away from earthly life, the world then hesitates to consult to philosophy in solving urgent problems. Basically, phi- losophy and ecology serve cooperation that results a strong relation between  knowledge and philosophy in this century. Philosophy as an alternative will not  rule out knowledge and religion roles. However, they are always in dialog. Like a  cycles, there is a need to each other support and logic explanation and cooperation  in facing life problems. The Ecology’s wisdom that is found in local wisdom,  ascetics of knowledge, and philosophy’s ethic are useful to be alternatives to  prevent nature and environment from destruction.